Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fcell.2022.904714
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of the cell wall by glycosylphosphatidylinositol-anchored proteins in Arabidopsis

Abstract: A polysaccharides-based cell wall covers the plant cell, shaping it and protecting it from the harsh environment. Cellulose microfibrils constitute the cell wall backbone and are embedded in a matrix of pectic and hemicellulosic polysaccharides and glycoproteins. Various environmental and developmental cues can regulate the plant cell wall, and diverse glycosylphosphatidylinositol (GPI)-anchored proteins participate in these regulations. GPI is a common lipid modification on eukaryotic proteins, which covalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Our previous studies have shown that there are substantial changes in the structure and distribution of arabinogalactan proteins (AGPs) correlated with the ongoing ripening process (Kutyrieva-Nowak et al, 2023a). As common components in the plant extracellular matrix, AGPs are attached to the plasma membrane via glycosylphosphatidylinositol (GPI) anchors in the C-terminal domain (Showalter, 2001; Lopez-Hernandez et al, 2020; Zhou, 2022; Leszczuk et al, 2023). The specific and mutable distribution of AGPs in the cell wall-plasma membrane continuum allows identification of the effects of these molecules on the specific arrangement of the cell wall assembly in fruit cells (Liu et al, 2015; Leszczuk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that there are substantial changes in the structure and distribution of arabinogalactan proteins (AGPs) correlated with the ongoing ripening process (Kutyrieva-Nowak et al, 2023a). As common components in the plant extracellular matrix, AGPs are attached to the plasma membrane via glycosylphosphatidylinositol (GPI) anchors in the C-terminal domain (Showalter, 2001; Lopez-Hernandez et al, 2020; Zhou, 2022; Leszczuk et al, 2023). The specific and mutable distribution of AGPs in the cell wall-plasma membrane continuum allows identification of the effects of these molecules on the specific arrangement of the cell wall assembly in fruit cells (Liu et al, 2015; Leszczuk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have shown that there are substantial changes in the structure and distribution of arabinogalactan proteins (AGPs) correlated with the ongoing ripening process ( Kalaitzis et al., 2023 ; Kutyrieva-Nowak et al., 2023a ). As common components in the plant extracellular matrix, AGPs are attached to the plasma membrane via glycosylphosphatidylinositol (GPI) anchors ( Showalter, 2001 ; Lopez-Hernandez et al., 2020 ; Zhou, 2022 ; Leszczuk et al., 2023 ). The specific and mutable distribution of AGPs in the cell wall-plasma membrane continuum allows identification of the effects of these molecules on the specific arrangement of the cell wall assembly in fruit cells ( Liu et al., 2015 ; Leszczuk et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Flotillins also play a key role in ER to PM-ND trafficking and endocytosis of nonspecific Lipid Transfer Proteins (nsLTPs) that are linked to the PM by glycosylphosphatidylinositol (GPI)anchors (47)(48)(49).…”
Section: Introductionmentioning
confidence: 99%
“…LatB seems to have a weaker effect on dynamin-dependent endocytosis of FLOT2 (FLOTILLIN 2; another nanodomain marker and binding partner of FLOT1 and aquaporins in Arabidopsis), and its mammalian homologs, which interact with cortical F-actin, dynamins and a range of regulatory proteins (25, 4146). Flotillins also play a key role in ER to PM-ND trafficking and endocytosis of nonspecific Lipid Transfer Proteins (nsLTPs) that are linked to the PM by glycosylphosphatidylinositol (GPI)-anchors (4749).…”
Section: Introductionmentioning
confidence: 99%